Perception and Behavior Analysis of Comorians Citizens on the Solid Household Waste Problems - Ali, Ali Issihaka; Karouach, Fadoua; Lahboubi, Nabila; Bakraoui, Mohammed; El Bari, Hassan (European Scientific Journal, ESJ, 2018)
The objective of this study is to analyze the perception of Comorian citizens facing the situation of solid waste management (SWM). For this, a qualitative and quantitative approach is conducted on a sample of 300 households. The study shows that 61.1% of households freely dispose a waste on sensitive sites, 19.7% bring waste to collection points and 18.6% benefit from door-to-door. Moreover, 63% of households prefer door-to-door as a means of waste disposal compared to 19.5% who prefer voluntary intake and 17.5% prefer free evacuation. Home sorting concerns only 19.3% of households compared with 80.7% whose dispose mixed waste. Households that are aware of the negative impact of waste on health are 87.5%, against 5%, are unconscious and 7.5% remain without opinion. The study also shows that 40% of households are aware of the negative impact of waste on the environment, against 33% of non-conscious and 27% of non-opinion. The majority of households (58%) are unsatisfied of waste collection services schedules. However, 93.3% of households approve actions carried out by NGO and association. A financial contribution for waste management system improvement of 0.54 USD and 1.08 USD per month was approved by 67% of households.